Social Perceptions of Konzo Disease in Nampula Province, Mozambique - Litos Raimundo; Daniela Rodrigues; Maria-Raquel G. Silva (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Konzo, a neurodegenerative disease prevalent in Nampula Province, Mozambique, presents debilitating symptoms known locally as “mantakassa” (“that which breaks legs”). Although the biomedical literature attributes its cause to insufficiently processed cassava amid food insecurity, traditional narratives often cite supernatural explanations, like witchcraft. This review analyzed the existing literature to understand social perceptions of konzo, focusing on traditional leaders’ perspectives and their implications for public health. It found that konzo cases cluster within families owing to shared dietary habits and socioeconomic vulnerabilities, disproportionately affecting women and children. Community narratives often link the disease to spiritual causes, differing from biomedical views. Health care workers noted low diagnostic accuracy and limited knowledge of the condition. Notably, the role of traditional healers, often the first line of care in rural areas, remains underdocumented, highlighting a critical knowledge gap. Further research into their understanding of konzo is essential for developing culturally sensitive health interventions and improving public health strategies.